The bond-slip constitutive model of retard-bonded prestressing steel strand. (15th February 2023) - Xiong, Xueyu; He, Linyi; Zhou, Ziwen; Xiao, Qisheng
Highlights: The residual branch of RPSR bond-slip curve is a downward sloping sinusoid. The guarantee rate of pullout failure of cylinder specimens is higher. The proposed model can reflect the whole process of the bond-slip relation of RPSR. The proposed model is in better agreement with the experimental curve than the existing models. Abstract: The bond property between the retard-bonded prestressing steel strand (RPSR) and concrete is the basis of mechanical behaviour of the retard-bonded prestressed concrete structure, which is of great significance to the theoretical design and engineering application of the retard-bonded prestressed concrete structure. In this paper, the center pullout test of RPSR was carried out, considering the influence of steel strand diameter, concrete strength, bond length and non-bond length. The results showed that the bond strength and peak point slip of RPSR are larger than that of the ordinary steel strand under the same condition. The residual branch of RPSR bond-slip curve was approximately a downward sloping sinusoid. The cylinder specimen had better confinable effect and was less prone to splitting failure. The conditions for pullout failure of RPSR were proposed. By establishing local coordinate system, the whole process bond-slip constitutive model of RPSR was proposed in this paper. It was found that the proposed model was in better agreement with the experimental results, which can reflect the whole process of the bond-slip relation between the RPSR and the concrete.